2014
DOI: 10.1371/journal.pone.0104771
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 Gene Silencing Ameliorates Diabetic Cardiomyopathy in a Type 2 Diabetes Rat Model

Abstract: BackgroundNucleotide-binding oligomerization domain-like receptor protein 3 (NLRP3) inflammasome is associated with metabolic disorder and cell death, which are important triggers in diabetic cardiomyopathy (DCM). We aimed to explore whether NLRP3 inflammasome activation contributes to DCM and the mechanism involved.MethodsType 2 diabetic rat model was induced by high fat diet and low dose streptozotocin. The characteristics of type 2 DCM were evaluated by metabolic tests, echocardiography and histopathology. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
252
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(275 citation statements)
references
References 49 publications
10
252
0
3
Order By: Relevance
“…Increasing of inflammation cytokines induces functional problems such as diastolic and systolic dysfunctions in diabetic cardiomyopathy (Adeghate et al 2010). Moreover, a depression of cardiac contractile function also promotes inflammatory cytokines release (Luo et al 2014). Previous study has shown that Sal B inhibits inflammatory factors release in vascular endothelial cells and in glial cells (Zhou et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing of inflammation cytokines induces functional problems such as diastolic and systolic dysfunctions in diabetic cardiomyopathy (Adeghate et al 2010). Moreover, a depression of cardiac contractile function also promotes inflammatory cytokines release (Luo et al 2014). Previous study has shown that Sal B inhibits inflammatory factors release in vascular endothelial cells and in glial cells (Zhou et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, the NLRP3 inflammasome is an attractive target to mitigate the inflammatory response associated with mitochondrial damage and metabolic stress that occurs in diabetes. In support of this concept, there are preclinical data demonstrating a protective effect of inflammasome inhibition in several models of cardiac injury (16,66,67,103). Although these data are provocative, further translational investigation is needed.…”
Section: Inflammationmentioning
confidence: 98%
“…It is now established that mitochondrial damage, particularly in the context of toll-like receptor activation with release of mitochondrial DNA and/or ROS, can activate the NLRP3 inflammasome, leading to the cleavage and release of IL-1b and IL-18 through a caspase 1-dependent mechanism (42,90,109). Emerging evidence suggests that the NLRP3 inflammasome is hyperactivated in diabetes and contributes to inflammatory damage in the heart and other tissues (56,66,68,100,101). Interestingly, excess FFA, hyperglycemia, and ischemic stress have been shown to promote inflammasome assembly by producing mitochondrial and/or lysosome damage (97,100,101).…”
Section: Inflammationmentioning
confidence: 99%
“…[122][123][124][125] Cardiac inflammation and leukocyte recruitment, as observed in the setting of diabetic cardiomyopathy, seems to be mediated in part through the NLRP3 inflammasome in a similar fashion to MI. 68,[126][127][128][129][130] It has been hypothesized that the mechanism of inflammasome activation in diabetic cardiomyopathy is dependent on the combination of oxidative stress and reactive oxygen species production, as a result of mitochondrial dysfunction. 131,132 Damaged mitochondria are removed from the cell in a process known as mitophagy, and if this system is overwhelmed or ineffective, increased reactive oxygen species ensues.…”
Section: Diabetic Cardiomyopathy and Chronic Inflammationmentioning
confidence: 99%